FACIAL NERVE ANATOMY - Rashidov Muhsin Narzi o’g’li (TADQIQOTLAR, 2025)
ABSTRACT . Facial nerve monitoring has been increasingly routinely used as an intraoperative adjunctive method to help the head and neck surgeon to identify and minimize facial nerve injury during parotid surgery. The goals, current applications, recent technical advances, and limitations of the method are reviewed. A main focus of this chapter is a review of several prospective clinical trials that have been performed in recent years that have analyzed the benefit of electrophysiological nerve monitoring during parotid surgery. It has been demonstrated that nerve monitoring reduces the risk of early postoperative facial nerve dysfunction in primary surgery, but not in revision surgery. The effect is more pronounced in total than in superficial parotidectomy. Monitoring is associated with shorter surgical times in primary superficial parotidectomy compared to total parotidectomy. Facial nerve stimulation at the completion of parotidectomy helps to prognosticate the facial nerve functional outcome. A lower postdissection to predissection ratio of the maximal response amplitude is associated with early postoperative facial dysfunction. Facial nerve monitoring also helps the surgeon to avoid facial nerve injury when the facial nerve is not exposed during parotid surgery, such as during extracapsular dissection of a parotid neoplasm or sentinel node biopsy.